Role of non-linear processes in conducting polymer blends for piezo-sensors Part 2: studies on polyaniline/SBS blends - Radhakrishnan, S; Kar, Swarnendu B. (Sensors and Actuators A-Physical, 2005)
The electrical properties and piezo-response of conducting polymer blends have been investigated with respect to composition for styrene-butadiene-styrene (SBS) elastomer containing two grades of polyaniline (PANI). The blends were synthesized using solution/dispersion technique in which the conducting PANI was prepared with either HCl or dodecyl benzene sulfonic acid (DBSA) as dopant. Thick sheets cast from these exhibited high piezo-sensitive electrical resistance even at small mechanical load. The pressure dependence of resistance followed a non-linear power law of the type R = KP-m where K and m values changed considerably with composition. The current voltage characteristics in these blends were found to be highly non-linear and the conduction mechanism was either space charge limited or tunneling type depending on the concentration and nature of conducting additive. These various results have been explained on the basis of the phenomenological model developed incorporating the non-linear processes for electrical and mechanical properties. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: conducting polymer; non-linear process; piezo-sensors